Most of the propeptide is dispensable for stability and autoprocessing of the zymogen of the germination protease of spores of Bacillus species. - Pedersen, L B (1997)
Loss of 3, 7, or 10 of the amino-terminal 15 residues removed upon autoactivation of the zymogen of the germination protease (GPR), which initiates protein degradation during germination of spores of Bacillus species, did not result in significant changes in (i) the lack of enzymatic activity of the zymogen, (ii) the rate of zymogen autoactivation, or (iii) the unreactivity of the zymogen's single SH group. Removal of 13 amino-terminal residues resulted in a partially active enzyme whose SH group was as reactive as the fully active enzyme. These findings suggest that at least a part of the propeptide blocks access to the enzyme's active site. However, the free propeptide did not inhibit the enzyme.